Developments in permafrost science and engineering in response to climate warming in circumpolar and high mountain regions, 2019–2024 - Burn, Christopher R. (2024)
Research in geocryology is currently principally concerned with the effects of climate change on permafrost terrain. The motivations for most of the research are (1) quantification of the anticipated net emissions of CO2 and CH4 from warming and thaw of near-surface permafrost and (2) mitigation of effects on infrastructure of such warming and thaw. Some of the effects, such as increases in ground temperature or active-layer thickness, have been observed for several decades. Landforms that are sensitive to creep deformation are moving more quickly as a result, and Rock Glacier Velocity is now part of the Essential Climate Variable Permafrost of the Global Climate Observing System. Other effects, for example, the occurrence of physical disturbances associated with thawing permafrost, particularly the development of thaw slumps, have noticeably increased since 2010. Still, others, such as erosion of sedimentary permafrost coasts, have accelerated. Geochemical effects in groundwater from trace elements, including contaminants, and those that issue from the release of sediment particles during mass wasting have become evident since 2020. Net release of CO2 and CH4 from thawing permafrost is anticipated within two decades and, worldwide, may reach emissions that are equivalent to a large industrial economy. The most immediate local concerns are for waste disposal pits that were constructed on the premise that permafrost would be an effective and permanent containment medium. This assumption is no longer valid at many contaminated sites. The role of ground ice in conditioning responses to changes in the thermal or hydrological regimes of permafrost has re-emphasized the importance of regional conditions, particularly landscape history, when applying research results to practical problems.